Efeito da Idade sobre a Fertilidade de Éguas Inseminadas com Sêmen Diluído, Resfriado a 14°C e Transportado - Valle, Guilherme Ribeiro; Da Silva Filho, José Monteiro; De Oliveira, Henrique Nunes [UNESP]; Palhares, Maristela Silveira; De Mello, Marcelo Avelar; Goloubeff, Bárbara (My University, 1999)
To study the effect of age upon ovulatory and fertility traits, 147 cycles of 99 mares were grouped in different age classes (1 - 3-6 years; 2 - 7-10 years; 3 - 11-14 years, and 4 - 15-19 years), according to the year of birth. The mares were inseminated with diluted, cooled and transported semen of one stallion only, three times a week (Monday, Wednesday and Friday). The follicular control, based on rectal palpation, and the teasing were conduced every day, during all the experimental period. For transportation the diluted semen in a skim milk-glucose extender at an insemination dose of 400 × 106 viable spermatozoa was used, before cooling, in the modified Celle container. The average semen collection time to the artificial insemination was 3.5 hours and the final temperature of the semen, at the artificial insemination time, of 14°C. There was no influence of the age on the follicular growth and the size of ovulatory foliculum. The fertility decreases after 15 years of age, with reduction of conception rate/cycle, pregnancy efficiency, however, none characteristics that indicate senescence up to 19 years of age were observed.
Effect of Age on Fertility in Mares Inseminated with Diluted, Cooled at 14°C and Transported Semen
Keywords: Age; Artificial insemination; Equine; Fertility